2007
DOI: 10.1080/01647950708683691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rust mitesCalepitrimerus vitis(Nalepa), bud mitesColomerus vitis(Pagenstecher) (Acari: Eriophyidae) and short shootsyndrome in Oregon vineyards

Abstract: -Short Shoot Syndrome (SSS) causes severe crop losses in Oregon vineyards due to bunch necrosis during the early part of the season. Other symptoms include malformed leaves, unusually short and angled shoots, scar tissue and bronzed leaves close to harvest time. This work shows that SSS found in Oregon vineyards is closely associated with grape leaf rust mite, Calepitrimerus vitis (Nalepa) infestations. Very few bud mites, Colomerus vitis (Pagenstecher), were found in the vineyards during the current year and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
1
21
2
6
Order By: Relevance
“…As perdas de produção decorrentes do ataque de C. vitis apresentam variação com o local e o nível de infestação. Na Austrália, BERNARD et al (2003) registraram perdas de até 13%, enquanto nos Estados Unidos da América, WALTON et al (2007) constataram até 24% de perdas na produção da videira, não havendo, até o momento, trabalhos de avaliação de perdas por C. vitis no Brasil.…”
Section: Nos Vinhedos Da Região Da Campanha Do Rio Grande Do Sul O áunclassified
See 1 more Smart Citation
“…As perdas de produção decorrentes do ataque de C. vitis apresentam variação com o local e o nível de infestação. Na Austrália, BERNARD et al (2003) registraram perdas de até 13%, enquanto nos Estados Unidos da América, WALTON et al (2007) constataram até 24% de perdas na produção da videira, não havendo, até o momento, trabalhos de avaliação de perdas por C. vitis no Brasil.…”
Section: Nos Vinhedos Da Região Da Campanha Do Rio Grande Do Sul O áunclassified
“…Devido ao reduzido tamanho, o método empregado para a coleta e a detecção de C. vitis apresenta papel decisivo tanto na pesquisa quanto em programas de controle (MONFREDA et al, 2010), sendo utilizados com frequência armadilhas adesivas (BERNARD et al, 2005;WALTON et al, 2007) (STRECK et al, 2008), no sistema de espaldeira, com espaçamento de 3,0m entre as fileiras e 1,0m entre as plantas, com histórico de infestação por C. vitis.…”
Section: Nos Vinhedos Da Região Da Campanha Do Rio Grande Do Sul O áunclassified
“…O ácaro-da-ferrugem-da-videira Calepitrimerus vitis (Nalepa) (Acari: Eriophyidae) está presente em vinhedos de Vitis vinifera (L.) em várias partes do mundo, causando atraso no desenvolvimento e secamento de flores, folhas e ramos (HLUCHÝ; POSPÍŠIL, 1992), promovendo perdas na produção de uvas de até 13% na Austrália (BERNARD et al, 2003a) a 24% nos Estados Unidos (WALTON et al, 2007). No Brasil, esta espécie foi relatada inicialmente em 1951, no Rio Grande do Sul, causando danos à cultura e, após um período sem ocorrência, voltou a ser encontrada na safra de 2004/2005, em vinhedos, na região da Campanha, no mesmo Estado (MORAES; FLECHTMANN, 2008).…”
Section: Introductionunclassified
“…In this region, grapevine rust mite Vitis Calepitrimerus (NALEPA, 1905) (Acari: Eriophyidae) has been mentioned as one of the main pests of this culture (KLOCK et al, 2011), which has also been reported in other producing countries (BERNARD et al, 2005;Walton et al, 2007Walton et al, , 2010. The species attacks only leaves (KLOCK et al, 2011;FERLA, 2012), being disseminated in the main grape producing regions of southern Brazil, but remains absent in the production pole of Petrolina / Juazeiro, main region of production of fine table grapes of Brazil (DOMINGOS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, the control of C. vitis has been carried out with the use of sulfur, which has reduced potential for selection of resistant populations and also has effect on Erysiphe necator Schwein, the fungus causing powdery mildew (BERNARD et al, 2005;WALTON et al, 2007), and synthetic acaricides such as spirodiclofen, fenpyroximate and fenazaquim (DUSO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%